'It's Just a Story': Pornography, Desire, and the Ethics of Fictive Imagining. (8th November 2017) - Bartel, Christopher; Cremaldi, Anna
Abstract: Is it ever morally wrong for a consumer to imagine something immoral? Brandon Cooke has recently argued that it cannot be. On Cooke's account, fictive imagining is immune to moral criticism because such cases of imagining do not amount to the consumer's endorsement of the immoral content, nor do they imply that the authors of such fictions necessarily endorse their contents. We argue against Cooke that in fact fictively imagining something immoral can be morally blameworthy for the consumer, specifically in cases where fictive imagining is engaged in the service of immoral desires. Taking one potent case—namely, rape-fantasy pornography—we argue that the proper engagement with pornography requires the engagement of the consumer's desires, and that consumers often engage with works of pornography as a way of 'trying on' desires. Insofar as it is morally wrong to desire something immoral, then it is also morally wrong to cultivate an immoral desire; and for some consumers, fictive imagining is a means of cultivating immoral desires. In this restricted sense, we argue that it can be morally wrong for a consumer to engage in fictively imagining immoral things.